The Role of Habit and Perceived Usefulness on the Continuance Intention of Subscription Video on Demand Services in Indonesia - Elisabet Patrisia Mangunsong; Nurdin Sobari (Eduvest - Journal of Universal Studies, 2024)
In the midst of the rising popularity of Subscription Video On Demand (SVOD), the industry faces significant challenges. The high churn rate and the abundance of competitors in the SVOD industry necessitate that service providers develop strategies to maintain consumer interest. Consumers who significantly contribute to the high churn rate are Generation Y and Generation Z, also known as digital natives. This study aims to analyze how factors within the Expectancy Confirmation Model can influence the Continuance Intention of SVOD users. This descriptive study employs a cross- sectional design. The respondents of this study consist of 159 active SVOD users. The findings reveal that confirmation and individual mobility significantly influence perceived usefulness. Additionally, confirmation, perceived usefulness, and perceived enjoyment significantly affect satisfaction. Furthermore, satisfaction, perceived usefulness, and habit are significant predictors of continuance intention. However, the influence of individual mobility and perceived enjoyment on continuance intention is not significant. Practically, this study provides insights for SVOD service providers to develop marketing strategies that enhance consumer habit and satisfaction. Academically, this study combines two models from previous researchs making the model and variables used more comprehensive in explaining the predictors of continuance intention.